ANALISIS PENGELOLAAN MODAL KERJA TERHADAP KINERJA KEUANGAN PADA PT. NURLENNI KAHAR SPBU 74.92212 KEC. GALESONG UTARA, KAB.TAKALAR - Syafaruddin, Syafaruddin; Septiani Amin, Amelia Rezky (COMPETITIVENESS, 2018)
This research aims to find out the Analysis of Working Capital Management at PT. NurlenniKahar gas station 74.92212. To find out the Profibility of PT. NurlenniKahar gas station 74.92212. To find out the Analysis of Working Capital Management against Profibility At Pt. Nurlenni Kahar gas station 74.92212. The type of research used in this research is descriptive quantitative (non statistic). To obtain the necessary data and information, the author conducted a study on PT. NurlenniKahar gas station 74.92212. From the results of research that has been done obtained results that (1) Management of working capital as measured by the cash turnover of inventory turnover in 2015 and 2016 shows this increase means the operation of the company PT. Nurlenni Kahar gas station 74.92212 has been effective in managing its working capital. (2) Profibility as measured by GPM, NPM, and OPM has increased, this means that the company in PT. Nurlenni Kahar gas station 74.92212 has been effective in carrying out its operations and the company is able to generate profit. (3) and lastly analysis of working capital management to profibility in PT. Nurlenni Kahar gas station 74.92212 has been effective, the increase in cash turnover and inventory turnover is accompanied by an increase in profibility obtained. Keywords: Working Capital and Profibility